IMPLEMENTASI ISAK 35, SISTEM PENGENDALIAN INTERNAL DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS - Dewi Laras Saraswati; Rine Rizky Yunisa; Alyani Agustina (Prodi Akuntansi, 2022)
This study aims to examine: the effect of the implementation of ISAK 35 on the quality of the financial statements of educational foundations in Bandung Regency, the effect of the internal control system on the quality of financial reports at educational foundations in Bandung Regency and the effect of the use of information technology on the quality of financial reports at educational foundations in Bandung Regency. The population of this study were all educational foundations in Bandung Regency, which amounted to 15 educational foundations and 26 schools under them. The sampling technique used in this research is using slovin method with the number of respondents as many as 60 people. This research method uses quantitative research methods with primary data obtained from questionnaire data which is measured using a Likert scale quantitative method. The data analysis technique used is a partial significance test (t test) with the SPSS 21.0 for windows program. The results of this study indicate that the implementation of ISAK 35 has a significant positive effect on the quality of financial reports, the internal control system has no effect on the quality of financial reports, the use of information technology has a significant positive effect on the quality of financial reports. quality of financial reports. The coefficient of determination from the implementation of ISAK 35, Internal Control System and Utilization of Information Technology is 66.5% of the Quality of Financial Statements and the remaining 33.5% is influenced by other factors.